Intention in Talmudic law between thought and deed - Strauch Schick, Shana (Boston Leiden Brill, 2021)
"In Intention in Talmudic Law: Between Thought and Deed, Shana Strauch Schick offers the first comprehensive history of intention in classical Jewish law (1st-6th centuries CE). Through close readings of rabbinic texts and explorations of contemporaneous legal-religious traditions, Strauch Schick constructs an intellectual history that reveals remarkable consistency within the rulings of particular sages, locales, and schools of thought. The book carefully traces developments across generations and among groups of rabbis, uncovering competing lineages of evolving legal and religious thought, and demonstrating how intention gradually became a nuanced, differentially applied concept across a wide array of legal realms"--
Keywords: Intention in rabbinical literature; Intention -- Religious aspects -- Judaism